2022
DOI: 10.3390/molecules27186075
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Portulaca oleracea on Streptozotocin-Induced Type I Diabetes-Associated Reproductive System Dysfunction and Inflammation

Abstract: Background: Type-one diabetes (T1D), a chronic autoimmune disease with marked inflammatory responses, is associated with infertility complications and implications. Based on the anti-diabetic, antioxidant, and anti-hyperlipidemic potential of Portulaca oleracea (PO), this study aimed to evaluate the protective effect of this plant extract on streptozotocin-induced type-I-diabetes-associated reproductive system dysfunction and inflammation. Methods: Male rats were randomly divided into four experimental groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…DM is a metabolic disease that poses a serious risk to public health and causes severe damage to a number of organs. This disease also regards as one of the important cause of morbidity and mortality worldwide Moreover, growing evidence suggests that DM is closely associated with fertility problems, particularly in the male [29]. In fact, previous clinical and pre-clinical studies have reported that DM causes serious disruptions in male reproductive function by paving the way for problems such as testicular tissue defects [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DM is a metabolic disease that poses a serious risk to public health and causes severe damage to a number of organs. This disease also regards as one of the important cause of morbidity and mortality worldwide Moreover, growing evidence suggests that DM is closely associated with fertility problems, particularly in the male [29]. In fact, previous clinical and pre-clinical studies have reported that DM causes serious disruptions in male reproductive function by paving the way for problems such as testicular tissue defects [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…This disease also regards as one of the important cause of morbidity and mortality worldwide Moreover, growing evidence suggests that DM is closely associated with fertility problems, particularly in the male [29]. In fact, previous clinical and pre-clinical studies have reported that DM causes serious disruptions in male reproductive function by paving the way for problems such as testicular tissue defects [29,30]. Similar to the literature, the results of our histopathological examination (JTBS) revealed that DM was dramatically disrupted histo-architecture of the testicular tissue and caused histopathological alterations such as seminiferous tubular atrophy, tubular degeneration, interstitial edema and Leydig cells losses.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes with induction in the secretion of inflammatory mediators by macrophage cells results in prolongation and an increase in inflammation, thereby delaying wound healing. [114][115][116][117][118][119][120][121] Therefore, the researchers fabricated CUR-loaded CTS NPs (CUR-CS-NPs) to evaluate their capability in a decrement in macrophage cellmediated inflammation and accelerating wound healing in a STZ-induced diabetic rat model. The findings revealed that CUR-CS-NPs with sustained drug release and better cell uptake, through the reduction in inflammation of macrophages and increment in angiogenesis, effectively accelerated the process of wound healing in comparison to the control group.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Diabetes with induction in the secretion of inflammatory mediators by macrophage cells results in prolongation and an increase in inflammation, thereby delaying wound healing 114–121 . Therefore, the researchers fabricated CUR‐loaded CTS NPs (CUR‐CS‐NPs) to evaluate their capability in a decrement in macrophage cell‐mediated inflammation and accelerating wound healing in a STZ‐induced diabetic rat model.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…The mice were twelve weeks old with a weight range of 30 g. They were kept under standard conditions, including 12h light-dark, room temperature (20°C) with 60 ± 10% humidity, and were provided with suitable nutrition until the initiation of the tests. Then they were randomly divided into eight groups (n = 6), including group 1: Control group that received only water and food and experienced no intervention; group 2: Diabetic control group that received only STZ without medication; group 3: Diabetic group in which a low dose of extracts (100 mg/kg) was injected intraperitoneally; group 4: Diabetic group in which a high dose of the extracts (300 mg/kg) was injected intraperitoneally (17); group 5: Diabetic group that received a low dose of extracts (100 mg/kg) by gavage (oral); group 6: Diabetic group in which 300 mg/kg of extracts was gavaged; group 7: Control group in which 300 mg/kg of extracts was gavaged; and group 8: The group that received STZ and gavaged with 300 mg/kg of extracts simultaneously (for five days) (17)(18)(19).…”
Section: Animalsmentioning
confidence: 99%